Qaluyaarmiuni Nunamtenek Qanemciput / Our Nelson Island Stories - Rearden, Alice (Book collections on Project MUSE., 2011)
The elders have mapped significant places to help perpetuate an active relationship between the land and the people who continue to rely on the fluctuating bounty of the Bering Sea coastal environment. Alice Rearden is the primary translator for the Calista Elders Council."--Description from Univ. of Washington Press